TANGGUNG JAWAB DEVELOPER UNTUK MENANGGUNG CACAT TERSEMBUNYI DALAM PERJANJIAN JUAL BELI RUMAH PERUMAHAN - Chandra Dewi Puspitasari (LPPM UNY, 2007)
In reality, not all houses offered by developers re I perfect condition. Many times, the houses sold are in broken condition. The damage is hidden so that buyers do not realize the real condition of the houses. This research involves 5 developers in Yogyakarta. According to REI (Real Estate Indonesia), they are reputable developers having project of more than 100 houses in all types. This research aims at knowing the developers’ responsibility toward the hidden damage of the houses sold. Based on the result of the research, the buyers know the damage after the transaction is done. Moreover, the exoneratie clausule states that the responsibility of the developers is limited to certain period so that the risk after the limited time is for the buyers. In addition, the maintenance period given by the developers varies so that the claims of the buyers also vary.